The effect of acute caffeine ingestion on physical performance in elite European competitive soccer match-play - Morgans, R.; Rhodes, D.; Orme, P.; Bezuglov, E.; Di Michele, R.; Teixeira, J.; Oliveira, R. (Scientific Journal of Sport and Performance, 2023)
The present study examined the effect of acute caffeine ingestion (150 mg) on the physical performance of elite European soccer players during official competitive match-play. The current investigation was a parallel-group design that collated data from a cohort of 19 male outfield players from an elite European soccer team (mean ± SD, age 26 ± 4 years; weight 80.5 ± 8.1 kg; height 1.83 ± 0.07 m; body-fat 10.8 ± 0.7%). Players were classified and matched by position and grouped accordingly: centre defender (CD) n = 5, wide defender (WD) n = 3, centre midfield (CM) n = 7, wide forward (WF) n = 2, and centre forward (CF) n = 2. For all performance variables, the mean values were compared in caffeine consumers vs. non consumers using independent-sample t-tests, with significance set at p < .05. Cohen`s d was used to quantify the effect size, and was interpreted as trivial (<0.2), small (0.2-0.5), medium (0.5-0.8), and large (>0.8). For all examined variables, there were trivial or small non-significant (p > .05) trivial or small differences between caffeine consumers and non-consumers. The findings of the present research did not confirm the study hypothesis, once running and accelerometry-based variables did not improve with the caffeine ingestion of 150 mg. Therefore, the caffeine supplement used in this study is not suggested for improving performance in the variables analysed.